2020
DOI: 10.1088/1755-1315/578/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Assessment of Different Landfill Leachate in Nepal

Abstract: Leachate analysis is a vital aspect of landfill operation & management, but limited studies have been conducted in Nepal in this regard. The study focuses on the chemical assessment of leachate’s characteristics of 4 different landfill sites in Nepal in the year 2019 among which 3 are operational and 1 closed, and their variation due to age, functionality, seasons, and feeding amount and waste composition. The data of leachate samples at two months’ interval was collected and assembled into 4 seasons viz. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These findings are in line with the research of Oumar et al [26], which revealed that landfill leachate has a pH value of 8.21. According to Adhikari and Khanal [27], the presence of methanogenic bacteria causes the pH value inside the landfill environment to vary depending on the age of the dump. As a result of these bacteria converting accumulated acids into methane and carbon dioxide, the rate of methane gas production will grow [28].…”
Section: Effect Of Leachate Ph On Metal Solubilitymentioning
confidence: 99%
“…These findings are in line with the research of Oumar et al [26], which revealed that landfill leachate has a pH value of 8.21. According to Adhikari and Khanal [27], the presence of methanogenic bacteria causes the pH value inside the landfill environment to vary depending on the age of the dump. As a result of these bacteria converting accumulated acids into methane and carbon dioxide, the rate of methane gas production will grow [28].…”
Section: Effect Of Leachate Ph On Metal Solubilitymentioning
confidence: 99%
“…The COD at the beginning of the measurement was very high but gradually decreased. This high COD was due to the presence of organic material in the waste, which broke down the organic compounds into smaller components dissolvable in the leachate [40]. Thus, the subsequent decrease in the COD suggests a short process of decomposition of the organic material [41].…”
Section: Biochemical Oxygen Demand (Bod)mentioning
confidence: 99%
“…Therefore, understanding and quantifying leachate contamination potential is essential in landfill operations and management. According to Adhikari et al (2020) and Abunama et al (2021), quantifying leachate contamination potential could be used for evaluation of the accuracy of landfill operation/exploitation and its impact on surrounding areas.…”
Section: Introductionmentioning
confidence: 99%